Aerogel and production method thereof
The method of forming silica aerogels with a continuous fibrous skeleton and controlled drying process addresses breakage issues, enabling large-sized aerogels with uniform structure and high yield for thermal insulation.
Patent Information
- Application Number
- JP2023102163
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-09
AI Technical Summary
Silica aerogels are prone to breakage during drying due to bending stress caused by volume contraction and restoration, especially when large-sized, leading to non-uniform pore structures and low yield.
A method involving a continuous fibrous skeleton structure and controlled drying process using normal pressure, where a silicon compound is hydrolyzed to form a sol, followed by crosslinking and solvent substitution with low surface tension solvents, and rocking the gel in a horizontal direction to maintain uniformity.
Produces large-sized silica aerogels with high yield and no defects, maintaining uniform pore structure and transparency, suitable for applications requiring large areas like thermal insulation.
Smart Images

Figure 2025002182000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aerogel and a method for producing the same. [Background technology]
[0002] Aerogel has a uniform mesoscale porous structure, high porosity (typically 90% or more), and low bulk density (0.004 to 0.500 g / cm 3 ), and extremely low thermal conductivity (20 mW / mK or less), and is typically produced by the sol-gel method. Among them, silica aerogel, which is an aerogel containing Si, has high visible light transmittance in addition to high thermal insulation properties obtained by low thermal conductivity, and is expected to be used as a transparent insulating material for residential windows (highly insulated double-glazed windows typically have a visible light transmittance of about 60%) and displays.
[0003] Silica aerogel is manufactured by hydrolyzing a monomer solution of a silane compound in a solvent such as water to produce a sol, crosslinking (condensation) the sol to form a gel (condensation compound), and then drying the gel. However, silica aerogel is very fragile and difficult to handle during manufacturing due to its high porosity and thin structure due to a microstructure composed of nanometer-order domains (typically 100 nm or less). In addition, in order to obtain large-sized silica aerogels, it is necessary to dry the gel using a supercritical drying method using high-temperature and high-pressure supercritical fluids, which requires expensive equipment for its manufacture.
[0004] Therefore, a method has been proposed in which the skeleton constituting the pore structure is given flexibility to avoid breakage due to shrinkage deformation or recovery deformation during the drying process, thereby enabling drying at normal pressure with low manufacturing costs. For example, Patent Document 1 describes a method of obtaining a transparent silica aerogel by drying at normal pressure by performing a reaction to generate a sol and a reaction to gel the sol in one step, thereby controlling the skeleton structure to be uniform and suppressing visible light scattering. In addition, Non-Patent Document 1 describes a method of obtaining a silica aerogel by drying at normal pressure by making the pore structure an organic-inorganic hybrid. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5250900 [Non-patent literature]
[0006] [Non-Patent Document 1] K. Kanamori, M. Aizawa, K. Nakanishi, T. Hanada, Adv. Mater., 19, 1589-1593 (2007) Summary of the Invention [Problem to be solved by the invention]
[0007] In the method for producing silica aerogel described in Patent Document 1 and Non-Patent Document 1, when the gel is dried, the inherent solvent present inside the gel is discharged from the gel, and the volume of the gel shrinks to 20% or less due to capillary force. However, when the inherent solvent present inside the gel is discharged to a certain extent, gas enters the pores of the gel, and the volume of the gel is restored to almost the same volume as before the shrinkage.
[0008] Here, when the volume of the gel shrinks and the shape of the gel is no longer similar to the shape before shrinkage, bending stress caused by deformation occurs in the gel, causing the gel to break, making it difficult to obtain an aerogel of the desired shape and size.
[0009] Furthermore, if the solvent remaining on the surface and inside of the shrunken gel is not discharged uniformly from the gel when the gel is dried, the solvent remaining in the gel will cause deformation and bending stress in the gel when the gel is restored to its volume, which will break the gel, making it difficult to obtain an aerogel of the desired shape and size.
[0010] In particular, when shrinking a large gel to obtain a large silica aerogel with dimensions of 300 mm square or more, not only does the bending stress due to deformation increase with the increase in dimensions, but the temperature distribution at each part after the sol is poured into the mold and the material flow caused by the temperature distribution tend to cause differences in the polycondensation conditions at each part, which tends to cause non-uniformity in the pore structure. As a result, the gel breaks due to non-uniform capillary forces caused by non-uniform pore sizes caused by the shrinkage of the volume when the gel is dried, making it virtually impossible to produce silica aerogel with a high yield by drying at normal pressure.
[0011] The present invention has been made in view of the above circumstances, and has an object to provide an aerogel that is in a sound state free of defects such as cracks and that can be produced with a high yield even in a relatively large area (specifically, a size including a square surface area of 300 mm on each side), by optimizing the parameter of total light transmittance when irradiated with visible light, and a method for producing the same. [Means for solving the problem]
[0012] In order to achieve the above object, the gist of the present invention is as follows.
[0013] (1) An aerogel containing Si, having a pore structure formed of a continuous fibrous skeleton in a mesh-like shape and a plurality of pores defined by the skeleton, the aerogel having at least a surface area of a square of 300 mm on each side, and having a standard deviation of total light transmittance of 0.60% or less when the surface area is irradiated with visible light having a wavelength of 550 nm, calculated as a thickness of 10 mm.
[0014] (2) The aerogel according to (1) above, wherein the total light transmittance when irradiated with visible light is 50% or more in terms of a thickness of 10 mm.
[0015] (3) The aerogel according to (1) or (2) above, which is produced by drying at normal pressure.
[0016] (4) A method for producing an aerogel, comprising: a sol production step of adding a silicon compound to an aqueous solution and hydrolyzing the silicon compound to produce a sol; a gelation step of injecting the sol into a casting dish and crosslinking the sol in the casting dish to produce a gel and curing the gel; a solvent washing and replacement step of supplying a first solvent having a low surface tension of 45 mN / m or less at 20°C into the casting dish and washing and replacing the inherent solvent present on the surface and inside of the gel with the first solvent; and a drying step of supplying a second solvent having a higher specific gravity than the first solvent and undergoing two-phase separation from the first solvent in the state where it is supplied into the casting dish and drying the second solvent to produce a Si-containing aerogel, wherein at least one of the gelation step, the solvent washing and replacement step, and the drying step is performed while the sol or the gel produced in the casting dish is held in the casting dish and oscillated in a lateral direction parallel to the bottom surface of the casting dish.
[0017] (5) The method for producing an aerogel according to (4) above, wherein each step from the gelling step to the drying step is carried out in the same reaction chamber.
[0018] (6) The method for producing an aerogel according to (4) above, wherein at least the gelling step and the drying step among the steps from the gelling step to the drying step are carried out in separate reaction chambers.
[0019] (7) The method for producing an aerogel according to (5) or (6) above, wherein the gelation step is carried out by adjusting the concentration of water vapor contained in the atmosphere in the reaction chamber to a range of 60% or more and 100% or less with respect to the saturated water vapor pressure.
[0020] (8) The method for producing an aerogel according to any one of (5) to (7) above, wherein the drying step is carried out by adjusting the vapor concentration of the solvent contained in the atmosphere in the reaction chamber to a range of 70% or more and less than 100%.
[0021] (9) The method for producing an aerogel according to any one of (5) to (8) above, wherein the drying step is carried out at normal pressure in the reaction chamber.
[0022] (10) An apparatus for producing an aerogel comprising: a casting dish in which a silicon compound is added to an aqueous solution, the resulting sol is subjected to a crosslinking reaction to produce a gel and the gel is cured; a casting means for injecting the sol into the casting dish; a first solvent supplying means for supplying a first solvent having a low surface tension of 45 mN / m or less at 20°C into the casting dish, and washing and replacing an inherent solvent present on the surface and inside of the gel with the first solvent; a second solvent supplying means for supplying a second solvent having a higher specific gravity than the first solvent and which undergoes two-phase separation from the first solvent into the casting dish; a drying means for drying the second solvent while it is supplied into the casting dish, thereby producing an aerogel containing Si; and a rocking mechanism for rocking the sol or gel formed in the casting dish in a horizontal rocking direction parallel to a bottom surface of the casting dish while the second solvent is held by the casting dish. Effect of the Invention
[0023] According to the present invention, in particular by optimizing the parameter of the total light transmittance when irradiated with visible light, it is possible to provide an aerogel that is in a sound state free of defects such as cracks and has a high yield even when it has a relatively large area (specifically, a size including a square surface area of 300 mm x 300 mm), and a method for producing the same. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a graph showing the relationship between the standard deviation of the total light transmittance and the rupture probability for the aerogel of the present invention when irradiated with visible light having a wavelength of 550 nm, with the standard deviation of the total light transmittance on the horizontal axis and the rupture probability of the aerogel on the vertical axis. [Diagram 2] FIG. 2 is a flow chart showing the order of steps in the method for producing an aerogel according to the present invention. [Diagram 3] Figure 3 is a conceptual diagram showing the state of the sol and gel in each step of the method for producing an aerogel according to the present invention up to the solvent washing and replacement step, where Figure 3(a) is a conceptual diagram showing the state of the sol and casting dish when the sol is injected into the casting dish in the gelling step, Figure 3(b) is a conceptual diagram showing the state of the gel and casting dish after the gelling step, Figure 3(c) is a conceptual diagram showing the state in which multiple casting dishes in the reaction chamber are immersed in a first liquid phase composed of the first solvent in the solvent washing and replacement step, and Figure 3(d) is a conceptual diagram showing the state after the first solvent that is not retained in the casting dish in the reaction chamber in the solvent washing and replacement step has been discharged. [Figure 4] Figure 4 is a conceptual diagram showing the state of the gel in the drying process among the various steps of the method for producing an aerogel according to the present invention. Figure 4(a) is a conceptual diagram showing the state in which the gel held in all of the casting dishes in the reaction chamber is immersed in the second liquid phase. Figure 4(b) is a conceptual diagram showing the state in which the first solvent and excess second solvent in the reaction chamber are discharged and the second solvent is supplied to multiple casting dishes in the drying process. Figure 4(c) is a conceptual diagram showing the state in which the aerogel that has finished drying in the drying process has floated to the interface of the second liquid phase. [Diagram 5]FIG. 5 is a schematic diagram showing an example of a reaction apparatus used in the method for producing an aerogel according to the present invention. [Figure 6] FIG. 6 is a graph showing the standard deviation of the total light transmittance when irradiated with visible light having a wavelength of 550 nm for each of the aerogels of the invention and the comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, specific embodiments of the present invention will be described in detail with reference to the drawings. Note that the present invention is not limited to the following embodiments, and various modifications are possible without departing from the gist of the present invention.
[0026] [About the composition of aerogel] The aerogel of the present invention is a Si-containing aerogel having a pore structure formed of a continuous fibrous skeleton in a mesh-like shape and a plurality of pores defined by this skeleton, the aerogel having at least a surface area of a square of 300 mm on each side, and a standard deviation of the total light transmittance when this surface area is irradiated with visible light having a wavelength of 550 nm, calculated as a 10 mm thickness, of 0.60% or less.
[0027] The inventors focused on the standard deviation of light transmittance at three points, namely, the center position of the square surface area, the corner positions of the square surface area, and the center positions of the sides of the square surface area, when visible light was irradiated onto a square surface area of a Si-containing aerogel, and found that, in one or both of the gelling step in which the sol is crosslinked to form a gel, and the drying step in which the gel is dried, the sol or gel formed in the casting dish is oscillated in a lateral oscillation direction parallel to the bottom surface of the casting dish while being held in the casting dish, thereby making it possible to reduce the variation in total light transmittance when visible light is irradiated onto the aerogel, even for a relatively large area. In this case, by optimizing the parameters of the total light transmittance when irradiated with visible light, more specifically, by setting the standard deviation of the total light transmittance when the aerogel is irradiated with visible light having a wavelength of 550 nm (hereinafter sometimes simply referred to as the "standard deviation of the total light transmittance") to 0.60% or less in terms of a 10 mm thickness, it is possible to produce aerogel that is in a healthy state without defects such as cracks, with a high yield, even for a relatively large area (specifically, a size including a square surface area of 300 mm on each side).
[0028] In this specification, the aerogel is "free of defects such as cracks" means that no defects such as cracks are visible when the aerogel is visually inspected, and more specifically means that there are no defects such as cracks having a length of 100 μm or more or pinholes having a length of 100 μm or more.
[0029] FIG. 1 is a graph showing the relationship between the standard deviation of the total light transmittance and the probability of breakage of the aerogel when irradiated with visible light having a wavelength of 550 nm, with the standard deviation of the total light transmittance on the horizontal axis and the probability of breakage of the aerogel on the vertical axis. In FIG. 1, when the standard deviation of the total light transmittance is changed, examples in which the aerogel breaks are plotted as "probability of breakage = 1", and examples in which the aerogel does not break are plotted as "probability of breakage = 0". Next, from these plots, a logistic regression curve was obtained with the standard deviation (%) of the total light transmittance as the explanatory variable and the presence or absence of breakage as the objective variable, and was depicted by a solid line in the graph of FIG. 1. At this time, when the standard deviation of the total light transmittance of the aerogel is 0.65% or less in terms of 10 mm thickness, the probability of breakage is below 0.5, and when the standard deviation of the total light transmittance of the aerogel is 0.60% or less in terms of 10 mm thickness, no examples of aerogel breakage were observed. Furthermore, when the standard deviation of the total light transmittance of the aerogel was 0.50% or less in terms of 10 mm thickness, the probability of breakage was almost 0 in the logistic regression curve. Therefore, the standard deviation of the total light transmittance of the aerogel is preferably 0.60% or less in terms of 10 mm thickness, and more preferably 0.50% or less. This is also clear from the fact that when a logistic regression curve is performed using the standard deviation of the total light transmittance as the explanatory variable and the presence or absence of breakage as the objective variable, the threshold value of the explanatory variable at which the probability of breakage is 50% is a value greater than 0.60%, as shown in Figure 1.
[0030] The specific configuration of the aerogel of the present invention will be described below.
[0031] Here, the aerogel of the present invention has at least a surface area of a square of 300 mm on each side. In an aerogel with such a large surface dimension, bending stress during contraction and restoration tends to be large, especially on the outside of the surface. Even in this case, the standard deviation of the total light transmittance when irradiated with visible light can be reduced, and thus aerogel in a sound state without defects such as cracks can be obtained with a high yield. Therefore, the aerogel can be preferably used in applications requiring a large area, such as insulation materials for construction.
[0032] In addition, the standard deviation of the total light transmittance of the aerogel of the present invention when a 300 mm square surface area of the surface is irradiated with visible light having a wavelength of 550 nm is 0.60% or less in terms of 10 mm thickness. Here, the 300 mm square surface area can be extracted, for example, by a 300 mm square that is located at a position overlapping with the center (center of gravity) of the aerogel. In addition, the measurement points of the total light transmittance in the surface area are not particularly limited, but from the viewpoint of evaluating the fragility of the aerogel when dried, for example, a plurality of points including the center and the periphery may be set from the 300 mm square surface area (particularly, the center position of the square, the corner positions of the square, and the center positions of the sides of the square (three points of the center positions of the sides connecting the adjacent corners of the square)).
[0033] In this regard, in a square aerogel, which is the most common shape for industrial products, the positions where the pore structure becomes non-uniform with respect to other positions (typically the center of the square) are often at the corners of the aerogel square and the center of the square side. In addition, the variation in total light transmittance based on the center of the square often appears in different forms at the corners of the square and the center of the square side depending on the manufacturing conditions (shape of the chamber, how the gels are arranged, how the temperature is transferred to the gel, the stirring method, etc.). Therefore, by taking the standard deviation of the total light transmittance at three points, the center of the square, the corners of the square, and the center of the square side, and reducing the standard deviation of these three points, it is possible to make the aerogel less likely to break when drying the gel. Therefore, by using an aerogel with a small standard deviation of the total light transmittance at these three points, it is possible to provide an aerogel in a sound state without defects such as cracks, with a high yield, even if it is relatively large in area.
[0034] The standard deviation of the total light transmittance is the standard deviation when the total light transmittance obtained at all measurement points is converted into a value for a thickness of 10 mm and used as the population.
[0035] In this way, by making the standard deviation of the total light transmittance when irradiated with visible light 0.60% or less in terms of 10 mm thickness, the mesh-like continuous fibrous skeleton contained in the pore structure of the aerogel is arranged approximately uniformly along the surface direction of the surface, so that the aerogel has high homogeneity and the gel, which is its precursor, also has high homogeneity. For example, when producing an aerogel using normal pressure drying, when the volume of the gel is shrunk during normal pressure drying of the gel, and when the volume of the gel is subsequently restored to obtain the aerogel, the shape of the gel can be shrunk and restored while maintaining a similar shape, so that bending stress due to deformation is unlikely to occur in the gel. Therefore, even if the aerogel of the present invention has a relatively large area, it can be produced in a high yield and in a sound state without defects such as cracks.
[0036] Furthermore, the aerogel of the present invention has a total light transmittance of preferably 50% or more, more preferably 70% or more, calculated as a 10 mm thickness, when a 300 mm square surface area of the surface is irradiated with visible light having a wavelength of 550 nm. This reduces the elements that absorb or reflect visible light in the aerogel, making it easier for inhomogeneous parts that cause bending stress to appear, making it even more difficult for bending stress to occur due to deformation.
[0037] The size of the aerogel of the present invention is a size including a surface area of a square of 300 mm on each side. Therefore, when the surface of the aerogel of the present invention is viewed in a plane, both the vertical and horizontal dimensions are 300 mm or more. On the other hand, the upper limit of the size of the aerogel of the present invention is not particularly limited, but one or both of the vertical and horizontal dimensions may be 5000 mm or 3000 mm when the surface is viewed in a plane.
[0038] The thickness of the aerogel of the present invention is not particularly limited, but the average thickness can be, for example, in the range of 1 mm to 30 mm. Here, the aerogel is preferably plate-shaped, and in particular, both sides are preferably flat, from the viewpoint of facilitating the contraction and restoration of the gel in the casting dish, and in this case, the thickness of the aerogel is preferably uniform.
[0039] The aerogel of the present invention has a Si-containing microstructure formed of a continuous fibrous skeleton in the form of a network and a plurality of pores defined by the skeleton.
[0040] Here, the microstructure of the aerogel is a microstructure containing silicon atoms in the molecule, and an example of such a microstructure is a polysilsesquioxane-based microstructure. Among these, the polysilsesquioxane-based microstructure can be formed by hydrolysis and polycondensation reaction of silicon alkoxide. In particular, polymethylsilsesquioxane (PMSQ, MeSiO 1.5PMSQ aerogel can be formed by the hydrolysis and polycondensation reaction of methyltrialkoxysilane (MeSi(OR)3) in combination with a surfactant as a phase separation inhibitor. Examples of the hydrolysis and polycondensation reaction in forming PMSQ aerogel include the hydrolysis reaction by an acid catalyst shown in the following formula (I) and the polycondensation reaction by a base catalyst shown in the following formula (II). MeSi(OR)3+3H2O → MeSi(OH)3+3ROH: Formula (I) MeSi(OH)3 → MeSiO 1.5 +1.5H2O: Formula (II)
[0041] In addition, the microstructure of aerogel has a continuous fibrous skeleton in a mesh-like shape, which forms a number of minute pores, thereby reducing the density of the aerogel and decreasing the thermal conductivity of the aerogel, thereby improving its thermal insulation.
[0042] Here, the average pore size of the multiple pores in the microstructure of the aerogel is not particularly limited, but can be, for example, in the range of 5 nm to 100 nm. Here, the average pore size of the pores can be the average inner diameter when the pores are approximated by tubes and the inner diameter of the tubes is approximated by a circle. The lower limit of the average inner diameter of the pores may be 5 nm or more, 7 nm or more, 10 nm or more, 20 nm or more, 30 nm or more, or 50 nm or more. The upper limit of the average inner diameter of the pores may be 100 nm or less, 90 nm or less, 80 nm or less, or 70 nm or less. Since the average pore size of the pores is a dimension equal to or less than the mean free path (MFP) of the element molecules constituting the air at atmospheric pressure, the aerogel placed in air at atmospheric pressure will be in a state where air has entered the inside of the pores.
[0043] The porosity of the aerogel, i.e., the ratio of the pore volume of the through holes (pores) to the total volume of the aerogel, is not particularly limited, but is preferably 70% or more. In particular, the porosity, the ratio of the pore volume of the through holes (pores) to the total volume of the aerogel, may be 75% or more, 80% or more, 85% or more, or 90% or more. Even when the aerogel of the present invention has such a high porosity, it can be obtained by drying at normal pressure.
[0044] The density of the aerogel is, for example, 0.15 g / cm 3 The density of the aerogel can be as low as 0.15 g / cm or less. Here, the density of the aerogel can be determined, for example, by mercury intrusion porosimetry. The lower the density of the aerogel, the smaller the thermal conductivity, and the better the thermal insulation. The density of the aerogel of the present invention can be as low as 0.15 g / cm or less. 3 Even if it is below this temperature, it is difficult to break, and the thermal conductivity at this time is small, at around 0.01 W / m·K to 0.02 W / m·K.
[0045] In addition to the above-mentioned configuration, the aerogel of the present invention may contain other components intended to provide functionality, improve appearance, and provide decorativeness. For example, it may contain an antistatic agent, a lubricant, an inorganic pigment, an organic pigment, an inorganic dye, an organic dye, and the like. In addition, the aerogel of the present invention may contain water, an organic solvent, a surfactant, a catalyst, and decomposition products thereof as unavoidable components in the production. In addition, the aerogel of the present invention may contain dust mixed in from the production space or production equipment as unavoidable components in the production.
[0046] [About the aerogel manufacturing process] As an example of a production method by which the above-mentioned aerogel can be obtained, the following method can be mentioned.
[0047] Fig. 2 is a flow chart showing the order of each step of the manufacturing method of the aerogel 1 according to the present invention. Fig. 3 is a conceptual diagram showing the state of the sol 11 and the gel 12 in the steps up to the solvent washing and replacement step S3 of the manufacturing method of the aerogel 1 according to the present invention, Fig. 3(a) is a conceptual diagram showing the state of the sol 11 and the casting dish 3 when the sol 11 is poured into the casting dish 3 in the gelation step S2, Fig. 3(b) is a conceptual diagram showing the state of the gel 12 and the casting dish 3 after the gelation step S2 is performed, Fig. 3(c) is a conceptual diagram showing the state in which a plurality of casting dishes 3 in the reaction chamber 2 are immersed in the first liquid phase L1 composed of the first solvent in the solvent washing and replacement step S3, and Fig. 3(d) is a conceptual diagram showing the state after the first solvent not held in the casting dish 3 in the reaction chamber 2 is discharged in the solvent washing and replacement step S3. FIG. 4 is a conceptual diagram showing the state of the sol 11 and the gel 12 in the steps of the method for producing an aerogel 1 according to the present invention, from the solvent washing and replacement step S3 onwards. FIG. 4(a) is a conceptual diagram showing the state in which the multiple casting dishes 3 in the reaction chamber 2 are immersed in the second liquid phase L2 composed of the second solvent in the solvent washing and replacement step S3. FIG. 4(b) is a conceptual diagram showing the state in which the first solvent and excess second solvent in the reaction chamber 2 are discharged and the second solvent is supplied into the multiple casting dishes 3 in the solvent washing and replacement step S3. FIG. 4(c) is a conceptual diagram showing the state in which the aerogel 1 that has been dried in the drying step S4 floats on the interface of the second liquid phase L2.
[0048] As shown in FIGS. 2 to 4, the method for producing the aerogel 1 of the present invention includes a sol formation step S1 in which a silicon compound is added to an aqueous solution and hydrolyzed to form a sol 11; a gelation step S2 in which the sol 11 is poured into a casting dish 3 and crosslinked in the casting dish 3 to form a gel (wet gel) 12 and cure the gel; and a gelation step S3 in which a first solvent having a low surface tension of 45 mN / m or less at 20° C. is supplied into the casting dish 3 in which the gel 12 has been formed, and the inherent solvent present on the surface and inside of the gel 12 is cured by the first solvent. The method includes a solvent washing and replacement step S3 in which washing and replacement are performed with a solvent, and a drying step S4 in which a second solvent, which has a higher specific gravity than the first solvent and undergoes two-phase separation from the first solvent, is supplied into a casting dish 3 and dried to form an aerogel 1 containing Si. At least one of the gelling step S2, the solvent washing and replacement step S3, and the drying step S4 is performed while the sol 11 or gel 12 formed in the casting dish 3 is oscillated in a lateral direction parallel to the bottom surface 31 of the casting dish 3 while being held in the casting dish 3.
[0049] In the method for producing the aerogel 1 of the present invention, in at least one of the gelation step S2, the solvent washing and replacing step S3, and the drying step S4, the sol 11 or gel 12 formed in the casting dish 3 is swung in a lateral direction parallel to the bottom surface 31 of the casting dish 3 while being held in the casting dish 3, so that the atmosphere in contact with the sol 11 or gel 12 flows relative to the sol 11 or gel 12 as a whole due to the swinging, thereby improving the uniformity of the environment (temperature, component concentration, and flow rate) around the sol 11 or gel 12. As a result, the homogeneity of the sol 11 or gel 12 after the gelation step S2 or the drying step S4 can be improved, and the homogeneity of the aerogel 1 can also be improved. Therefore, it is possible to obtain an aerogel 1 with a small standard deviation of the total light transmittance when irradiated with visible light.
[0050] In this regard, a method of applying a driving force to a fluid (gas or liquid) constituting the environment to make the environment uniform is generally used to agitate the fluid. However, when applying a driving force to a fluid constituting the environment, the driving force is significantly attenuated depending on the distance from the application point of the driving force and the shape of the space, and therefore the driving force cannot be uniformly propagated to the entire environment surrounding the sol 11 or gel 12. In this regard, in the manufacturing method of the aerogel 1 of the present invention, the sol 11 or gel 12, rather than the fluid constituting the environment, is rocked while held in the casting dish 3, so that the entire sol 11 or gel 12 can be rocked as it is, thereby making the environment surrounding the sol 11 or gel 12 uniform.
[0051] At this time, since gel 12 is particularly fragile, it is not desirable to vigorously shake gel 12 in random directions including the thickness direction. Even in this case, by taking advantage of the fact that gel 12 has a two-dimensional shape (plate shape) held by casting dish 3, casting dish 3 holding gel 12 can be swung along a plane parallel to bottom surface 31 of casting dish 3, making it possible to make gel 12 less likely to break even if it is swung relatively vigorously.
[0052] Here, the rocking of the casting dish 3 holding the sol 11 or gel 12 is preferably completed within a limited space such as the reaction chamber 2, and is preferably performed continuously, so that the rocking is preferably a rotational motion. As an example, as shown in Fig. 5 described later, the casting dish 3 (or the casting dish holder 30 holding the casting dish 3) is placed in the reaction chamber 2 so that the surface of the sol 11 or gel 12 (the bottom surface 31 of the casting dish 3) is horizontal, and the reaction chamber 2 is rotated alternately clockwise and counterclockwise about the height direction Y of the reaction chamber 2 as the axis (central axis M), whereby the casting dish 3 holding the sol 11 or gel 12 can be rocked in a lateral rocking direction parallel to the bottom surface 31 of the casting dish 3.
[0053] In addition, when the sol 11 or gel 12 is swung in the lateral direction by a rotational motion along a certain direction, the fluid constituting the environment around the sol 11 or gel 12 flows in synchronization with the rotational motion due to frictional resistance with the sol 11 or gel 12, so that the relative speed of the swing with respect to the sol 11 or gel 12 may be attenuated. Therefore, from the viewpoint of suppressing this, it is preferable to change the swing speed of the casting dish 3 in at least one direction. This can increase the uniformity of the environment in contact with the surface of the sol 11 or gel 12, and can also increase the uniformity of the environment in contact with the sol 11 or gel 12 held in the different casting dishes 3, particularly when a plurality of casting dishes 3 are swung in the same device. At this time, when changing the swing speed of the casting dish 3, the swing direction may be reversed, but in particular when the swing of the casting dish 3 is due to a rotational motion, only the swing speed of the casting dish 3 may be changed without changing the swing direction. In addition, the swing speed of the casting dish 3 may be temporarily changed to zero, thereby making the swing of the casting dish 3 intermittent. The oscillation speed may be changed periodically or at regular intervals.
[0054] When the casting dish 3 is swung in the lateral direction by a rotational motion with the center of the casting dish 3 holding the sol 11 or gel 12 as the center of rotation, the relative speed between the sol 11 or gel 12 and the fluid constituting the surrounding environment depends on the distance from the center of rotation, so there is a risk that the swinging will be insufficient near the center of rotation. Therefore, from the viewpoint of further improving the uniformity of the environment around the sol 11 or gel 12, it is preferable to complicate the motion when swinging the casting dish 3. As an example, the casting dish 3 may be swung by making the casting dish holder 30 holding the casting dish 3 perform a planetary motion along the surface direction of the surface of the sol 11 or gel 12. In this way, by constantly changing the swinging direction and swinging speed of the casting dish 3, the uniformity of the environment in contact with the sol 11 or gel 12 held in the casting dish 3 can be further improved. Among these, from the viewpoint of further enhancing the uniformity of the environment in contact with the sol 11 or gel 12 held in the casting dish 3, it is preferable to repeatedly change the direction of motion to the opposite direction when performing planetary motion of the casting dish holder 30.
[0055] 3, the casting dish holder 30 may be arranged so that a plurality of casting dishes 3 are arranged in the thickness direction of the aerogel 1 to be obtained. This makes it possible to reduce the area of the casting dish holder 30 along the surface direction of the aerogel 1, and therefore makes it easier to rock the casting dish 3 holding the sol 11 or gel 12.
[0056] The manufacturing apparatus used in the manufacturing method of the aerogel 1 of the present invention is preferably one in which each step from the gelation step S2 to the drying step S4 is performed in the same reaction chamber 2. This eliminates the need to open the reaction chamber 2 between the sol generation step S1, the gelation step S2, the solvent washing and replacement step S3, and the drying step S4, so that it is possible to suppress the inhomogeneity of the sol 11 or gel 12 due to the time lag until the reaction chamber 2 follows the sudden environmental change when opening it, in the same sol 11 or gel 12. In addition, since it is no longer necessary to move the sol 11 or gel 12 between the devices for each step of the sol generation step S1, the gelation step S2, the solvent washing and replacement step S3, and the drying step S4, it is possible to prevent the breakage of the gel 12, especially when the gel 12 is moved.
[0057] On the other hand, the manufacturing apparatus used in the manufacturing method of the aerogel 1 of the present invention may be one in which at least the gelling step S2 and the drying step S4 among the steps from the gelling step S2 to the drying step S4 are performed in separate reaction chambers. This allows the time-consuming gelling step S2 and the drying step S4 to be performed separately in the manufacturing process of the aerogel 1, so that the aerogel 1 can be manufactured more efficiently. Even in this case, from the viewpoint of preventing damage due to rapid drying of the gel, it is preferable to perform the solvent washing replacement step S3 and the drying step S4 in the same reaction chamber.
[0058] Each step of the method for producing the aerogel 1 of the present invention will be described below.
[0059] [Sol generation process S1] Among these, the sol generating step S1 is a step of adding at least a silicon compound to an aqueous solution and hydrolyzing the solution to generate a sol 11. The sol 11 for producing the aerogel 1 of the present invention contains a siloxane bond, and can be generated by hydrolysis of the silicon compound by adding various raw materials including a silicon compound (main raw material) to a predetermined aqueous solution and stirring and mixing the raw materials.
[0060] The silicon compound as the raw material may be a silane compound, and more specifically, may be at least one of a difunctional silane compound, a trifunctional silane compound, and a tetrafunctional silane compound.
[0061] Here, a bifunctional silane compound refers to a silane compound having two siloxane bonds, a trifunctional silane compound refers to a silane compound having three siloxane bonds, and a tetrafunctional silane compound refers to a silane compound having four siloxane bonds.
[0062] Examples of bifunctional silane compounds include dialkoxysilane and diacetoxysilane. Desirable embodiments of dialkoxysilane include those in which the alkoxy group has 1 to 9 carbon atoms. Specific examples include dimethyldimethoxysilane, diethyldimethoxysilane, and diisobutyldimethoxysilane. These compounds may be used alone or in combination. In the present invention, it is particularly preferable to use dimethyldimethoxysilane (DMDMS) as the bifunctional silane compound.
[0063] Examples of the trifunctional silane compound include trialkoxysilane and triacetoxysilane. A preferred embodiment of the trialkoxysilane is one in which the alkoxy group has 1 to 9 carbon atoms. Examples of the trialkoxysilane include methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, pentyltriethoxysilane, hexyltriethoxysilane, and octyltriethoxysilane. These compounds may be used alone or in combination. In the present invention, it is particularly preferable to use methyltrimethoxysilane (MTMS) as the trifunctional silane compound.
[0064] Examples of the tetrafunctional silane compound include tetraalkoxysilane and tetraacetoxysilane. A preferred embodiment of the tetraalkoxysilane is one in which the alkoxy group has 1 to 9 carbon atoms. Examples include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. These silane compounds may be used alone or in combination. In the present invention, it is particularly preferable to use tetramethoxysilane (TMOS) as the tetrafunctional silane compound.
[0065] In the sol generating step S1, in addition to the silicon compound (main raw material), a surfactant, an acid, and an organic solvent can be used as auxiliary raw materials.
[0066] Among these, the surfactant contributes to the formation of the pore structure of the aerogel 1 in the gel formation process described below. Examples of surfactants that can be used in the production of the aerogel 1 include nonionic surfactants and ionic surfactants. Examples of ionic surfactants include cationic surfactants, anionic surfactants, and amphoteric surfactants. Among these, nonionic surfactants can be preferably used.
[0067] The amount of surfactant added will vary depending on the type and mixing ratio of silicon compounds and the type of surfactant, but can be, for example, in the range of 0.001 parts by mass to 100 parts by mass relative to 100 parts by mass of the total amount of silicon compounds as the main raw material. In particular, the range of 0.01 parts by mass to 90 parts by mass is preferred, and the range of 0.1 parts by mass to 80 parts by mass is even more preferred.
[0068] In addition, the acid acts as a catalyst during hydrolysis, and can accelerate the reaction rate of the hydrolysis. Specific examples of the acid include inorganic acids, organic acids, and organic acid salts. These acids may be used alone or in combination of two or more kinds.
[0069] Among these, examples of inorganic acids include hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, hydrofluoric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, bromic acid, chloric acid, chlorous acid, and hypochlorous acid. Examples of organic acids include carboxylic acids such as acetic acid, formic acid, propionic acid, oxalic acid, malonic acid, succinic acid, citric acid, malic acid, adipic acid, and azelaic acid. Examples of organic acid salts that can be used include acid aluminum phosphate, acid magnesium phosphate, and acid zinc phosphate. In the present invention, it is preferable to use acetic acid, which is an organic acid, as the acid.
[0070] The concentration of the acid added to the sol 11 obtained in the sol formation step S1 can be, for example, in the range of 0.0001 mol / L to 0.1 mol / L, preferably in the range of 0.0005 mol / L to 0.05 mol / L, and more preferably in the range of 0.001 mol / L to 0.01 mol / L.
[0071] As the organic solvent, alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol, 2-butanol, and t-butanol can be preferably used. These may be used alone or in combination of two or more. From the viewpoint of compatibility, the amount of organic solvent added to the solution to be prepared may be, for example, in the range of 4 mol to 10 mol per mol of the total amount of the silicon compound, which is the main raw material, and is particularly preferably in the range of 4.5 mol to 9 mol, and more preferably in the range of 5 mol to 8 mol.
[0072] The temperature of the solution and the stirring time in the sol generation step S1 depend on the types and amounts of the silicon compound, surfactant, water, acid, organic solvent, etc. contained in the mixed solution, but may be in the range of 0.05 hours to 48 hours in a temperature environment of 0° C. to 70° C., and preferably 0.1 hours to 24 hours in a temperature environment of 20° C. to 50° C. As a result, the silicon compound is hydrolyzed to form a colloid, and the sol 11 can be generated.
[0073] The secondary materials and / or decomposition products of the secondary materials used in the sol generating step S1 may be mixed into the produced aerogel 1 as unavoidable components.
[0074] [Gelling step S2] The gelation step S2 is a step of injecting the sol 11 generated in the sol generation step S1 into the casting dish 3, crosslinking the sol in the casting dish 3 to form a gel 12, and curing the gel. In this step, the sol 11 is injected into the casting dish 3 as shown in Fig. 3(a), and then the gel 12 is formed in the casting dish 3 as shown in Fig. 3(b). Here, the gelation step S2 can be broadly divided into a catalyst addition step S21 of adding a basic catalyst to the sol 11, a casting step S22 of injecting the sol 11 with the basic catalyst added into the casting dish 3, and a curing step S23 of curing the solution in the casting dish 3 to generate the gel 12.
[0075] Among these, the basic catalyst to be added to the sol 11 in the catalyst addition step S21 includes ammonium compounds such as ammonium hydroxide, ammonium fluoride, ammonium chloride, and ammonium bromide, alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide, basic sodium phosphates such as sodium metaphosphate, sodium pyrophosphate, and sodium polyphosphate, allylamine, diallylamine, triallylamine, isopropylamine, diisopropylamine, ethylamine, diethylamine, triethylamine, 2-ethylhexylamine, 3-ethoxypropylamine, diisobutylamine, 3-(diethyl)-2-propanol ...(diethyl)-2-propanol, 2-(diethyl)-2-propanol, 2-(diethyl)-2-propanol, 2-(diethyl Examples of the basic catalyst include aliphatic amines such as 3-(dimethylamino)propylamine, di-2-ethylhexylamine, 3-(dibutylamino)propylamine, tetramethylethylenediamine, t-butylamine, sec-butylamine, propylamine, 3-(methylamino)propylamine, 3-(dimethylamino)propylamine, 3-methoxyamine, dimethylethanolamine, methyldiethanolamine, diethanolamine, and triethanolamine, and nitrogen-containing heterocyclic compounds such as morpholine, N-methylmorpholine, 2-methylmorpholine, piperazine and its derivatives, piperidine and its derivatives, and imidazole and its derivatives. Here, the basic catalyst may be used alone or in combination of two or more kinds.
[0076] The basic catalyst may be a nitrogen compound that generates a basic catalyst when heated. The nitrogen compound is added as a compound that generates a basic catalyst when heated in the casting step S22 or the curing step S23. Specific examples include amide compounds such as urea, formamide, N-methylformamide, N,N-dimethylformamide, acetamide, N-methylacetamide, and N,N-dimethylacetamide, and heterocyclic compounds such as hexamethylenetetramine. Of these, urea can be preferably used in that it can increase the gel generation rate in the curing step S23. These nitrogen compounds that generate a basic catalyst when heated can generate a basic catalyst by heating in the curing step S23, so these nitrogen compounds may be added in the sol generation step S1 without performing the catalyst addition step S21.
[0077] Among these, an aqueous solution of ammonium hydroxide is preferred because it has a high reaction-promoting effect as a catalyst, can advance the crosslinking reaction from the sol 11 to the gel 12 in a short time, and can form the gel 12 with few defects. In addition, an aqueous solution of ammonium hydroxide is highly volatile, so it volatilizes in the solvent washing and replacement step S3 and the drying step S4 described below, and is therefore not likely to remain in the obtained aerogel 1.
[0078] The amount of the basic catalyst added to the sol 11 is preferably in the range of 0.5 parts by mass to 5 parts by mass, and more preferably in the range of 1 part by mass to 4 parts by mass, relative to 100 parts by mass of the total amount of the sol 11. If the amount of the basic catalyst added is less than 0.5 parts by mass, the crosslinking reaction cannot proceed when forming the gel 12 from the sol 11, and if the amount of the basic catalyst added is more than 5 parts by mass, the crosslinking reaction may proceed too quickly, resulting in a non-uniform gel 12.
[0079] The casting step S22 is a step of injecting the sol 11 to which the basic catalyst has been added into the casting dish 3, and is a step for obtaining the desired shape of the aerogel product. Here, the casting dish 3 can be made of either metal or synthetic resin, but from the viewpoints of non-combustibility in consideration of plant operation, flatness of the shape, and releasability, a dish in which a base material made of metal is coated with a release coating layer is preferably used. Here, examples of metals include iron alloys such as stainless steel and steel. Examples of the release coating layer include a coating layer made of a fluorine-based resin such as Teflon (registered trademark).
[0080] The casting dish 3 has a shape corresponding to the desired aerogel product. For example, when obtaining a plate-shaped aerogel 1, a concave tray with an opening at one end can be used as a mold. Here, the surface of the casting dish 3 is preferably flat from the viewpoint of facilitating contraction and restoration of the gel in the casting dish 3.
[0081] The curing step S23 is a step of curing the sol 11 filled in the casting dish 3 within the casting dish to generate a gel 12 and molding the gel 12 to fit the shape of the inner wall of the casting dish 3.
[0082] In the curing step S23, a predetermined energy is applied for a predetermined time to promote a crosslinking reaction from the sol 11 to the gel 12. Here, an example of the energy is thermal energy, and more specifically, heating to a temperature range of 30°C to 90°C, preferably 40°C to 80°C, can be mentioned. Here, the heating may be performed by a heater, or may be steam heating using water vapor or organic solvent vapor. These energy means may be used alone or in combination.
[0083] The time required for curing in the curing step S23 depends on the composition of the silicon compound, the types and amounts of surfactant, water, acid, organic solvent, basic catalyst, etc., and the type and density of energy used in the curing step S23, but can be in the range of 0.01 hours to 7 days, for example. Here, if the type of basic catalyst and the type of energy are optimized, gelation may be completed in the range of 0.01 hours to 24 hours. Curing may also be curing in which heat (temperature) and time are changed in multiple stages.
[0084] In the curing step S23, hot water may be supplied into the reaction chamber 2 and immediately discharged to form a water layer on the surface of the gel 12 to prevent cracks caused by drying. In addition to the hot water supplied into the reaction chamber 2 in the curing step S23, the liquid supplied into the reaction chamber 2 in the method for producing the aerogel 1 of the present invention is preferably a liquid having a temperature difference of 10° C. or less with respect to the atmospheric temperature of the reaction chamber 2, from the viewpoint of preventing damage to the gel 12. That is, at least one of the hot water used in the curing step S23, the cleaning agent used in the cleaning treatment S24 described later, the first solvent used in the solvent cleaning and replacement step S3, and the second solvent used in the drying step S4 is preferably supplied into the reaction chamber 2 with a temperature difference of 10° C. or less with respect to the atmospheric temperature of the reaction chamber 2.
[0085] Here, the curing step S23 is preferably performed by adjusting the concentration of water vapor contained in the atmosphere in the reaction chamber 2 to a range of 60% to 100% of the saturated water vapor pressure, and more preferably to a range of 80% to 100%. This appropriately controls the evaporation of water from the gel 12 in the gelling step S2, and therefore makes it possible to suppress the gel 12 from becoming non-homogenous due to the evaporation of water contained in the gel 12.
[0086] In addition, in the curing step S23, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3. This improves the uniformity of the temperature of the gel 12, and thus the homogeneity of the pore structure of the gel 12 can be further improved. As a result, when the internal solvent is discharged from the gel in the drying step S4 described later, the homogeneity of the pore structure (pore size) is improved, and the capillary force is generated in a nearly uniform state, so that the gel can be dried and shrunk to a shape close to a similar shape. In particular, from the viewpoint of improving the uniformity of the concentration of water vapor contained in the atmosphere near the gel 12 and further improving the homogeneity of the pore structure of the gel 12, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3 while adjusting the concentration of water vapor contained in the atmosphere in the reaction chamber 2 to the above range.
[0087] The materials used in the gelation step S2 and decomposition products of the materials may be mixed into the produced aerogel 1 as unavoidable components.
[0088] After the gelation step S2, a washing treatment S24 may be further performed to wash away the acid used to produce the sol 11, the catalyst used to produce the gel 12, reaction by-products, and the like.
[0089] A wide variety of organic solvents can be used as the cleaning agent used in the cleaning process S24, and it is particularly preferable to use a solvent different from the first solvent described below. Here, as the cleaning agent, for example, various organic solvents such as methanol, ethanol, n-propanol, isopropanol, 1-butanol, 2-butanol, t-butanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, xylene, 1,2-dimethoxyethane, acetonitrile, hexane, toluene, diethyl ether, chloroform, ethyl acetate, tetrahydrofuran, methylene chloride, N,N-dimethylformamide, dimethyl sulfoxide, acetic acid, and formic acid can be used. The above organic solvents may be used alone or in combination of two or more.
[0090] Among these, it is preferable to use, as the cleaning agent, methanol, ethanol, isopropanol, acetone, methyl ethyl ketone, etc., which are soluble in both the organic solvent constituting the first solvent described below and water, either alone or in combination of two or more kinds.
[0091] The cleaning in the cleaning process S24 can be performed by filling the reaction chamber 2 with a cleaning agent, immersing the multiple casting dishes 3 on which the gels 12 have been formed in the cleaning agent, and then discharging at least the methanol that is not retained in the casting dishes 3. This allows the acid and reaction by-products contained in the gels 12 to be washed away and discharged to the outside of the gels 12. At this time, the cleaning agent may remain in the casting dishes 3 because it is soluble in the first solvent described later.
[0092] Here, the cleaning process S24 is preferably performed by adjusting the concentration of the cleaning agent contained in the atmosphere in the reaction chamber 2 to a range of 80% to 100% of the saturated vapor pressure, and more preferably to a range of 90% to 100%. This suppresses the evaporation of the cleaning agent from the gel 12 in the cleaning process S24, and therefore makes it possible to suppress the gel 12 from becoming non-homogenous due to the evaporation of the cleaning agent contained in the gel 12.
[0093] In addition, in the cleaning process S24, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3. This increases the uniformity of the temperature of the gel 12 and the uniformity of the flow rate of the cleaning agent in contact with the gel 12, thereby further increasing the homogeneity of the pore structure of the gel 12. In particular, from the viewpoint of increasing the uniformity of the concentration of the cleaning agent contained in the atmosphere near the gel 12 and further increasing the homogeneity of the pore structure of the gel 12, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3 while adjusting the concentration of the cleaning agent contained in the atmosphere in the reaction chamber 2 to be within the above range.
[0094] The amount of the cleaning agent used in the cleaning process S24 depends on the temperature for solvent substitution and the apparatus (reaction chamber 2 and casting dish 3), but it is preferable to use an amount that allows all of the gels 12 to be entirely immersed in the cleaning agent supplied to the casting dish 3. Therefore, it is preferable to use an amount of the cleaning agent that is in the range of 2 to 100 times the total volume of the gels 12. Moreover, the cleaning process S24 is not limited to being performed once, and may be performed multiple times.
[0095] [Solvent washing and replacement process S3] The solvent washing and replacement step S3 is a step of supplying a first solvent having a low surface tension of 45 mN / m or less at 20°C into the casting dish 3 in which the gel 12 has been formed, and washing and replacing the inherent solvent and surfactant present on the surface and inside of the gel 12 with the first solvent. This allows the water and / or organic solvent, which is the inherent solvent present on the surface and inside of the gel 12, to be replaced with an organic solvent suitable for drying in a short time.
[0096] In the solvent washing and replacement step S3, the gel 12 is washed with a first solvent having a surface tension of 45 mN / m or less at 20° C., and the water (or organic solvent) on the surface and inside of the gel 12 is replaced with the first solvent in order to suppress shrinkage damage to the gel 12 in the drying step S4 described below. As the first solvent, a liquid having a surface tension of 45 mN / m or less at 20° C. can be used, and examples of such a liquid include dimethyl sulfoxide (43.5 mN / m), cyclohexane (25.2 mN / m), isopropanol (21 mN / m), heptane (20.2 mN / m), and pentane (15.5 mN / m).
[0097] The first solvent used in the solvent washing and replacement step S3 may have a surface tension at 20°C of 45 mN / m or less, 40 mN / m or less, 35 mN / m or less, 30 mN / m or less, 25 mN / m or less, 20 mN / m or less, or 15 mN / m or less, and may have a surface tension at 20°C of 5 mN / m or more, 10 mN / m or more, 15 mN / m or more, or 20 mN / m or more. Among these, it is particularly preferable to use an organic solvent containing an aliphatic hydrocarbon having a surface tension at 20°C in the range of 20 mN / m to 40 mN / m as the first solvent. Such organic solvents may be used alone or in combination of two or more kinds as the first solvent.
[0098] Moreover, the first solvent used in the solvent washing and replacement step S3 preferably has a property that the gel 12 settles and is immersed in the first liquid phase L1 constituted by the first solvent after the solvent washing and replacement step S3 is performed. For this reason, the first solvent preferably has affinity with the gel 12 and has a smaller specific gravity than the gel 12. Here, the fact that the first solvent has affinity with the gel 12 means that the solvent can penetrate into the pores of the gel 12, and as a result, the gel 12 can be impregnated with the solvent. An example of such a solvent is a solvent having a solubility parameter in the range of 7.0 to 9.5.
[0099] Furthermore, as the first solvent used in the solvent washing and replacement step S3, it is preferable to use a solvent having a lower specific gravity and a lower boiling point than the second solvent described below. From this viewpoint, it is preferable to use an organic solvent having a boiling point of 50° C. to 100° C. as the first solvent, and examples thereof include hydrocarbon solvents such as hexane (specific gravity 0.65, boiling point 69° C.) and heptane (specific gravity 0.68, boiling point 98° C.) and ester solvents such as methyl acetate (specific gravity 0.93, boiling point 57° C.) and ethyl acetate (specific gravity 0.90, boiling point 77° C.).
[0100] The solvent washing and replacement step S3 can be performed by filling the reaction chamber 2 with the first solvent, immersing a plurality of casting dishes 3 in which the gels 12 have been formed, in the first liquid phase L1 constituted by the first solvent, as shown in Fig. 3(c), and then discharging the first solvent that is not held in the casting dishes 3, as shown in Fig. 3(d). This allows impurities such as acid and reaction by-products contained in the gels 12 and the cleaning agent to be washed out and discharged to the outside of the reaction chamber 2. In addition, the gels 12 after the solvent washing and replacement step S3 are placed in a liquid phase system constituted by the first liquid phase L1 in the casting dishes 3.
[0101] Here, the solvent washing and replacement step S3 is preferably performed by adjusting the concentration of the first solvent contained in the atmosphere in the reaction chamber 2 to a range of 80% to 100% relative to the saturated vapor pressure, and more preferably to a range of 90% to 100%. This suppresses the evaporation of the first solvent from the gel 12 in the solvent washing and replacement step S3, and therefore makes it possible to suppress the gel 12 from becoming non-homogenous due to the evaporation of the first solvent contained in the gel 12.
[0102] In the solvent washing and replacement step S3, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3. This increases the uniformity of the temperature of the gel 12 and increases the uniformity of the flow rate of the solvent in the first liquid phase L1 in contact with the gel 12. This allows the pore structure of the gel 12 to be washed (removal of surfactants, etc.) in a more uniform state, and further increases the homogeneity of the pore structure of the gel 12. As a result, when the internal solvent is discharged from the gel in the drying step S4 described later, the uniformity of the pore structure (pore size) is increased, and capillary force is generated in a more uniform state, allowing the gel to be dried and shrunk to a shape close to a similar shape. In particular, from the viewpoint of increasing the uniformity of the concentration of the first solvent contained in the atmosphere in the vicinity of the gel 12 and further increasing the homogeneity of the pore structure of the gel 12, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3 while adjusting the concentration of the first solvent contained in the atmosphere in the reaction chamber 2 to within the above range.
[0103] The amount of the first solvent used in the solvent washing and replacement step S3 depends on the temperature and the apparatus (reaction chamber 2 and casting dish 3) at which the solvent is replaced, but it is preferable to use an amount that allows all of the gels 12 to be entirely immersed in the first liquid phase L1 in the casting dish 3. Therefore, it is preferable to use an amount of the first solvent that is in the range of 2 to 100 times the total volume of the gels 12. Furthermore, the solvent replacement in the solvent washing and replacement step S3 is not limited to being performed once, and may be performed multiple times. Furthermore, the specific method of the solvent replacement in the solvent washing and replacement step S3 may be any of full replacement, partial replacement, and circulatory replacement.
[0104] In particular, when the solvent exchange is performed multiple times, the type of organic solvent, the temperature, and the processing time may be set independently for each time. Here, in the solvent washing and replacement step S3, the solvent used in the last solvent replacement becomes the first solvent constituting the first liquid phase L1 described later.
[0105] The materials used in the solvent washing and replacement step S3 and / or decomposition products of the materials may be mixed into the produced aerogel 1 as unavoidable components.
[0106] [Drying process S4] The drying step S4 is a step of drying a second solvent, which has a higher specific gravity than the first solvent and undergoes two-phase separation from the first solvent, while being supplied into the casting dish 3, to form a Si-containing aerogel 1. Here, the drying step S4 can include at least the following steps of a first step S41, a second step S42, and a third step S43, which are carried out on the gel placed in the casting dish 3 having the first liquid phase L1 composed of the first solvent and after the solvent cleaning and replacement step S3. 1) A first step S41 of supplying a second solvent having a higher specific gravity than a first solvent and capable of undergoing two-phase separation from the first solvent into a reaction chamber 2 in which a casting dish 3 is placed 2) A second step S42 of removing the first solvent constituting the first liquid phase L1 from the reaction chamber 2. 3) A third step S43 of drying the gel 12 at a low temperature until the gel 12 floats to the interface of the second liquid phase L2.
[0107] Here, the drying step S4 is preferably performed by adjusting the vapor concentration of the solvent contained in the atmosphere in the reaction chamber 2 to a range of 70% or more and less than 100% of the saturated vapor pressure, and more preferably to a range of 90% or more and less than 100%. More specifically, of the third step S43 and the fourth step S44 of the drying step S4, at least the third step S43 is preferably performed by adjusting the total vapor concentration of the first solvent and the second solvent contained in the atmosphere in the reaction chamber 2 to the above range. This appropriately controls the evaporation speed of the first solvent and the second solvent from the first liquid phase L1, the second liquid phase L2, and the gel 12, so that the breakage of the gel 12 due to the sudden evaporation of the solvent contained in the gel 12 can be suppressed.
[0108] In addition, in the drying step S4, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3. More specifically, among the third step S43 and the fourth step S44 of the drying step S4, it is preferable to oscillate the gel 12 held in the casting dish 3 in a lateral oscillation direction parallel to the bottom surface 31 of the casting dish 3 at least in the third step S43. This increases the uniformity of the temperature of the gel 12 and increases the uniformity of the temperature distribution, vapor concentration distribution, and flow rate distribution in the atmosphere in the reaction chamber 2. Therefore, it is possible to increase the uniformity of the evaporation rates of the first and second solvents from the first liquid phase L1, the second liquid phase L2, and the gel 12. As a result, when the solvent contained in the gel 12 is discharged out of the gel, the uniformity of the pore structure (pore size) is increased, so that the capillary force is generated in a nearly uniform state, and the gel can be dried and shrunk to a shape close to a similar shape. Furthermore, when the pore structure is swelled by springback, the uniformity of the migration speed of the solvent vapor in the pores is increased, thereby increasing the uniformity of the pore structure (pore size), thereby improving the homogeneity of the obtained aerogel 1. From the viewpoint of further increasing the homogeneity of the obtained aerogel 1 by also increasing the uniformity of the vapor concentration of the solvent contained in the atmosphere in the vicinity of the gel 12, it is preferable to rock the gel 12 held in the casting dish 3 in a horizontal rocking direction parallel to the bottom surface 31 of the casting dish 3 while adjusting the vapor concentration of the solvent contained in the atmosphere in the reaction chamber 2 to the above range.
[0109] Moreover, the drying step S4 is preferably performed under normal pressure in the reaction chamber 2. This allows the drying of the gel 12 to be performed without applying pressure, and therefore the aerogel 1 can be produced with a simpler device than in the conventional drying step using a supercritical fluid, thereby reducing the production cost of the aerogel 1.
[0110] (1st step S41) The first step S41 is a step of supplying a second solvent, which has a higher specific gravity than the first solvent and undergoes two-phase separation from the first solvent, into the casting dish 3. As a result, the gel 12 is positioned in a liquid phase system having a first liquid phase L1 and a second liquid phase L2.
[0111] Here, the first solvent constituting the first liquid phase L1 and the second solvent constituting the second liquid phase L2 are selected so as not to completely mix with each other and to separate into two phases. In addition, a solvent having a higher specific gravity than the first solvent is selected as the second solvent, thereby forming a liquid phase system in which the first liquid phase L1 is located on top and the second liquid phase L2 is located on the bottom.
[0112] Furthermore, it is preferable to use a solvent having a boiling point higher than that of the first solvent as the second solvent, but this is not limited to this as long as the first liquid phase L1 evaporates first at the first temperature described below and a state in which the gel 12 is immersed in the second liquid phase L2 can be created.
[0113] The second solvent used in the first step S41 is preferably one that is capable of forming a phase-separated state into a first liquid phase L1 and a second liquid phase L2 without completely mixing with the first solvent, and has a boiling point higher than that of the first solvent. Examples of such a solvent include water (specific gravity 1.0, boiling point 100°C), silicone oil (specific gravity 0.94 to 0.98, boiling point 150°C or higher), fluorine-based solvents (specific gravity 1.3 to 1.5, boiling point 98 to 150°C), and mercury (specific gravity 13, boiling point 356°C).
[0114] The amount of the second solvent used in the first step S41 is preferably an amount that allows all of the gels 12 held in the casting dish 3 to be immersed in the second liquid phase L2. As a result, as shown in Fig. 4(a), the interface between the first liquid phase L1 and the second liquid phase L2 is located above the gels 12 held in the casting dish 3, and the first solvent that constituted the first liquid phase L1 can be easily removed.
[0115] (2nd process S42) The second step S42 is a step of removing the first solvent constituting the first liquid phase L1 from the reaction chamber 2. As a result, the first liquid phase L1 disappears, and the second solvent is supplied into the multiple casting dishes 3.
[0116] Here, it is preferable that the first solvent is discharged in a liquid state to the outside of the reaction chamber 2. This allows the first solvent to be quickly discharged to the outside of the reaction chamber 2.
[0117] On the other hand, the first solvent may be discharged in a gaseous state to the outside of the reaction chamber 2 by evaporating at a temperature higher than room temperature. The temperature at this time is preferably in the range of 30° C. to 50° C. Note that it is not preferable to set the temperature at this time to a temperature equal to or higher than the boiling point of the first solvent, since the gel 12 will break due to boiling of the first solvent.
[0118] In the second step S42, it is preferable to remove the first solvent constituting the first liquid phase L1 from the reaction chamber 2 and also remove the excess second solvent. In particular, from the viewpoint of quickly discharging the first and second solvents to the outside of the reaction chamber 2, it is preferable to discharge the first solvent in a liquid state together with the excess second solvent to the outside of the reaction chamber 2. At this time, since the first solvent having a low specific gravity remains inside the pores of the gel 12, as shown in FIG. 4(b), the second solvent is supplied to the multiple casting dishes 3, and the gel 12 in the casting dish 3 is partially immersed in the second liquid phase L2 and floats on the top of the second liquid phase L2. It is also observed that the gel 12 at this time is in a contracted state in the second liquid phase L2. By floating the gel 12 on top of the second liquid phase L2 in this manner, friction between the gel and the substrate can be reduced to almost zero when the gel shrinks in the second step S42 and when the volume is restored in the third step S43 and the fourth step S44 described below.
[0119] (3rd step S43) The third step S43 is a step of drying the gel 12 at a low temperature until the gel 12 floats to the interface of the second liquid phase L2. The gel 12 before the third step S43 is located in the second liquid phase L2, but the gel 1 that was contracted in the second step S42 recovers in volume by swelling the pore structure due to springback. Therefore, an aerogel 1 having the desired high homogeneity can be obtained.
[0120] The ambient temperature in the third step S43 is preferably in the range of 30°C to 60°C. By maintaining the temperature in this range, the second solvent remaining inside the gel 12 evaporates and the drying of the gel 12 progresses, so that the specific gravity of the gel 12 decreases, and the gel 12 moves upward from the liquid surface of the second liquid phase L2, and finally, as shown in FIG. 4(c), a dried aerogel 1 floating above the second liquid phase L2 can be obtained. Note that it is not preferable to set the temperature at this time to a temperature equal to or higher than the boiling point of the second solvent, because the gel 12 will break due to the boiling of the second solvent.
[0121] The third step S43 is preferably continued until the recovery of the volume of the gel 12 due to spring back reaches a steady state.
[0122] (4th step S44) After the third step S43, the aerogel 1 is preferably taken out of the liquid phase and further dried in a fourth step S44. By further performing the fourth step S44, the transparency of the aerogel 1 can be further increased.
[0123] Here, the drying conditions for the aerogel 1 are not particularly limited, and for example, the aerogel 1 may be naturally dried in the air. Among them, from the viewpoint of further increasing the transparency of the aerogel 1, it is preferable to dry the aerogel 1 at a high temperature of a second temperature higher than the first temperature.
[0124] When the aerogel 1 is dried at a high temperature at the second temperature, the second temperature is preferably in the range of 50° C. to 250° C. As conditions for high-temperature drying, the second temperature may be set in the range of 50° C. to 100° C. and the drying time may be set in the range of 5 hours to 10 hours. Alternatively, the second temperature may be set in the range of 150° C. to 250° C. and the drying time may be set in the range of 10 minutes to 90 minutes.
[0125] [Other processes] The above-mentioned manufacturing method has been described as a method for manufacturing a plate-shaped (or rectangular parallelepiped) aerogel, but the present invention is not limited thereto, and may include processing a plate-shaped aerogel into a desired shape as an optional step. For example, a plate-shaped aerogel can be processed into various shapes such as a film, a cube, a sphere, a cylinder, a pyramid, a cone, etc., in addition to different shapes of plates. Known mechanical processing means such as wire cutting and laser cutting can be used as a means for processing the aerogel.
[0126] The aerogel 1 of the present invention may include an optional process of processing a bulk aerogel, such as a plate-like aerogel, into granular aerogel. As a means for processing into granular aerogel, a known crusher (crusher) such as a jaw crusher, a roll crusher, or a ball mill can be used.
[0127] [Configuration of aerogel manufacturing equipment] The manufacturing apparatus 10 for manufacturing the aerogel 1 of the present invention is preferably used in the above-mentioned manufacturing method, and as shown in FIG. 5, includes a casting dish 3 for adding a silicon compound to an aqueous solution, hydrolyzing the resulting sol 11, crosslinking the sol 11 to form a gel 12 and curing the gel 12, a casting means 4 for injecting the sol 11 into the casting dish 3, and a first solvent L10 having a low surface tension of 45 mN / m or less at 20° C. is supplied into the casting dish 3 in which the gel 12 has been formed, and an internal solvent L10 existing on the surface and inside of the gel 12 is cured. The apparatus includes a first solvent supplying means 5 for washing and replacing the solvent with a first solvent L10, a second solvent supplying means 6 for supplying a second solvent L20, which has a specific gravity greater than that of the first solvent L10 and undergoes two-phase separation from the first solvent L10, into the casting dish 3, a drying means 7 for drying the second solvent L20 while it is supplied into the casting dish 3 to form an aerogel containing Si, and a rocking mechanism 8 for rocking the sol 11 or gel 12 formed in the casting dish 3 in a horizontal rocking direction parallel to the bottom surface of the casting dish 3 while it is held by the casting dish 3. As a result, an aerogel having a standard deviation of total light transmittance of 0.60% or less when irradiated with visible light having a wavelength of 550 nm in 10 mm thickness can be obtained as the aerogel 1, and therefore it is possible to manufacture aerogel having a relatively large area (specifically, a size including a surface area of a square of 300 mm square) in a sound state without defects such as cracks, with a high yield.
[0128] Here, as the casting means 4, the first solvent supplying means 5 and the second solvent supplying means 6, pipes equipped with valves (not shown) can be used.
[0129] The drying means 7 can include at least a drainage means 71 used to perform the second step S42 of the drying process S4 described above, which removes the first solvent constituting the first liquid phase L1 from the reaction chamber 2 as drainage liquid L3, and a temperature adjustment means 72 used to perform the third step S43 of the drying process S4, which adjusts the atmospheric temperature in the reaction chamber 2 until the gel 12 floats to the interface of the second liquid phase L2.
[0130] Furthermore, as the rocking mechanism 8, a mechanism that rocks the reaction chamber 2 in a lateral direction parallel to the bottom surface of the casting dish 3 can be used, and particularly in the embodiment in which the reaction chamber 2 is rotated along the rotation axis M as shown in Figure 5, a known driving means such as a motor can be used.
[0131] [Applications of aerogel] Because of these advantages, the aerogel 1 of the present embodiment can be preferably used as a thermal insulation material in cryogenic containers, the space field, the construction field, the automobile field, the home appliance field, the semiconductor field, industrial facilities, etc. In addition to its use as a thermal insulation material, the aerogel 1 of the present embodiment can also be used for water repellency, sound absorption, vibration silencing, catalyst support, and other purposes. EXAMPLES
[0132] Next, in order to further clarify the effects of the present invention, examples of the present invention and comparative examples will be described, but the present invention is not limited to these examples.
[0133] <Example of the present invention> [Sol generation process S1] As a surfactant, 3.28 g of a nonionic surfactant (BASF: Pluronic PE10500) was dissolved in 28.96 g of 0.005 mol / L acetic acid aqueous solution, and then 4.00 g of urea (Nacalai Tesque) was added as a compound that generates a basic catalyst and dissolved. 10.00 g of a silicon compound, which is the main raw material, was added to this aqueous solution, and the mixture was stirred and mixed at room temperature for 60 minutes to carry out a hydrolysis reaction of the silicon compound, producing Sol 11.
[0134] Here, the silicon compounds used were tetramethoxysilane (methyl orthosilicate manufactured by Tama Chemical Industries Co., Ltd., hereinafter sometimes abbreviated as "TMOS"), which is a tetrafunctional silane compound, methyltrimethoxysilane (DOWSIL Z-6366 Silane manufactured by Toray Dow Corning Co., Ltd., hereinafter sometimes abbreviated as "MTMS"), which is a trifunctional silane compound, and dimethyldimethoxysilane (Tokyo Chemical Industry Co., Ltd., product code: D1052, hereinafter sometimes abbreviated as "DMDMS"), which is a bifunctional silane compound, and were added in the proportions of 25% by mass of the tetrafunctional silane compound, 65% by mass of the trifunctional silane compound, and 10% by mass of the bifunctional silane compound. Both TMOS and MTMS were purified by vacuum distillation before use.
[0135] [Gelling step S2] Then, in the casting process S22, 1,225 ml of the generated sol 11 was poured into a casting dish 3 having a planar shape of a square of 320 mm on each side and a height of 17.5 mm to a depth of 10 mm, and the casting dish 3 poured with the sol 11 was placed in a casting dish holder 30.
[0136] Each of the subsequent steps from the gelation step S2 to the drying step S4 was carried out in the same reaction chamber 2. Here, as shown in Fig. 5, the casting dish 3 (or the casting dish holder 30 holding the casting dish 3) was placed in the reaction chamber 2 so that the surface of the sol 11 or gel 12 (the bottom surface of the casting dish 3) was horizontal, and the reaction chamber 2 was rotated around the height direction Y of the reaction chamber 2 as an axis (central axis M) so that the casting dish 3 holding the sol 11 or gel 12 swung in a lateral direction along the bottom surface 31 of the casting dish 3. In addition, water was poured below the casting dish 3 in the reaction chamber 2 so that the concentration of water vapor contained in the atmosphere in the reaction chamber 2 became equal to the saturated water vapor pressure.
[0137] In the curing step S23, the sol 11 poured into the casting dish 3 was left to stand at 60° C. for 10 hours to generate a basic catalyst by heating and gelate the sol 11, and then hot water at 60° C. was supplied into the reaction chamber 2 and immediately discharged to form a water layer with a thickness of 7.5 mm on the upper surface of the gel 12, and then the temperature inside the reaction chamber 2 was raised to 80° C. and the gel was allowed to mature by standing for 72 hours. At this time, the rocking mechanism 8 was operated to alternately rotate the reaction chamber 2 about the central axis M to a rotation angle of 90° in 20 seconds clockwise and to a rotation angle of 90° in 20 seconds counterclockwise, thereby rocking the casting dish 3 holding the sol 11 before gelation or the gel 12 after gelation in a horizontal rocking direction.
[0138] After the curing step S23, the rotation of the reaction chamber 2 was stopped, the rocking of the casting dish 3 was stopped, and the temperature inside the reaction chamber 2 was lowered to 60°C. Next, the reaction chamber 2 was filled with methanol (MeOH) at 60°C in an amount (about 6.2 L) equivalent to five times the volume of the gel, so that the inside of the casting dish 3 in which the gel was formed was immersed in methanol, and after maintaining this state for eight hours, the methanol not held in the casting dish 3 was discharged, and a cleaning process S24 was repeated five times to wash away surfactants, acids, reaction by-products, etc. contained in the gel. At this time, the rocking mechanism 8 was operated to alternately rotate the reaction chamber 2 clockwise around the central axis M to a rotation angle of 90° in 20 seconds and rotate the reaction chamber 2 counterclockwise to a rotation angle of 90° in 20 seconds, thereby rocking the casting dish 3 in which the gel 12 was held in the horizontal rocking direction. The methanol used in the cleaning treatment S24 was manufactured by Nacalai Tesque, Inc.
[0139] [Solvent washing and replacement process S3] Next, in the solvent washing and replacement step S3, isopropanol and heptane were used in this order as the first solvent. More specifically, isopropanol was supplied as the first solvent into the casting dish 3 in which the gel 12 was formed, and the inherent solvent present on the surface and inside of the gel 12 was washed and replaced with isopropanol, and then heptane was supplied as the first solvent into the casting dish 3, and the solvent such as isopropanol present on the surface and inside of the gel 12 was washed and replaced with heptane. This process was repeated twice. Here, the supply of the first solvent into the casting dish 3 was carried out by supplying the first solvent at 60° C. in an amount (about 6.2 L) equivalent to five times the gel volume into the reaction chamber 2 in which the gel 12 and the casting dish 3 were placed under the condition of 60° C., so that the multiple casting dishes 3 in the reaction chamber 2 were immersed in the first liquid phase L1 composed of the first solvent, as shown in FIG. 3(c), and this state was maintained for 8 hours. At that time, the rocking mechanism 8 was operated to alternately rotate the reaction chamber 2 about the central axis M to a rotation angle of 90° in 20 seconds clockwise and then rotate the reaction chamber 2 to a rotation angle of 90° in 20 seconds counterclockwise, thereby rocking the casting dish 3 holding the gel 12 in a horizontal rocking direction. After that, as shown in FIG. 3(d), the first liquid phase L1 that was not held in the casting dish 3 in the reaction chamber 2 was discharged. After the solvent washing and replacement step S3, the gel 12 in the casting dish 3 was immersed in the first liquid phase L1 composed of heptane and was submerged in the first liquid phase L1.
[0140] [Drying process S4] After the solvent washing and replacement step S3, the temperature inside the reaction chamber 2 was lowered to 40°C. Next, in the first step S41 of the drying step S4, water was used as the second solvent and water was supplied into the casting dish 3. Here, the supply of water into the casting dish 3 was carried out by supplying water at 40°C in an amount equivalent to five times the volume of the gel into the reaction chamber 2 in which the gel 12 and the casting dish 3 were placed, so that, as shown in FIG. 4(a), the multiple casting dishes 3 in the reaction chamber 2 were immersed in the second liquid phase L2 composed of water, and a liquid phase system was formed in which heptane (forming the first liquid phase L1 located on the upper side) and water (forming the second liquid phase L2 located on the lower side) were separated into two liquid phases at the interface above the gel 12.
[0141] Immediately after the first step S41, in the second step S42, the heptane and excess water in the reaction chamber 2 were discharged. At this time, as shown in Fig. 4(b), the gel 12 in the casting dish 3 contained heptane inside the pores and was partially immersed in the second liquid phase L2 composed of water, and was floating on the top of the second liquid phase L2.
[0142] After the second step S42, in the third step S43, the atmospheric temperature in the reaction chamber 2 was maintained at 40° C. to dry the gel 12 at a low temperature. More specifically, the gas in the reaction chamber 2 was continuously exhausted by an exhaust device at an exhaust speed of 500 ml / min, and the heptane vapor contained in the exhaust gas was collected by a cooler, and then the dry gas heated to 40° C. was returned to the reaction chamber 2 to dry the gel 12. At this time, the upper surface of the open container was covered with cellulose filter paper (Whatman filter paper grade 1, particle retention capacity 11 μm) as an air permeable membrane, and the total vapor concentration of the first solvent and the second solvent in the space partitioned by the heptane liquid level and the air permeable membrane was adjusted to be about 50%. In the third step S43 of this drying process S4, the rocking mechanism 8 was operated to alternately rotate the reaction chamber 2 clockwise around the central axis M to a rotation angle of 90° in 20 seconds, and then rotate the reaction chamber 2 counterclockwise to a rotation angle of 90° in 20 seconds, thereby rocking the casting dish 3 holding the gel 12 in a horizontal direction.
[0143] The low-temperature drying of the gel 12 in the third step S43 was carried out until the dried gel 12 floated to the liquid surface of the second liquid phase L2, and the drying time was about 45 hours. As a result, a translucent aerogel was obtained.
[0144] After the third step S43, the aerogel was further dried in a fourth step S44 in an additional incubator (IS601 manufactured by Yamato Scientific Co., Ltd.) at a drying temperature of 80°C until the size of the aerogel recovered to 95% of the size of the casting dish 3 (a size of 304 mm square), thereby obtaining an aerogel 1 according to the present invention.
[0145] Furthermore, these operations were repeated 26 times to obtain a total of 27 sheets of aerogel 1. Among these 27 sheets of aerogel 1, those in which the type and amount of surfactant added in the sol generation step S1, the ratio of TMOS, MTMS, and DMDMS in the silicon compound, the maturation time in the gelation step S2, the temperature, time, number of cycles, and rocking speed in the solvent washing and replacement step S3, and the temperature, exhaust speed, and rocking speed in the drying step S4 were changed were also included.
[0146] <Comparative Example> The sol 11 was poured into the casting dish 3, which was then placed in the casting dish holder 30. In this example, the casting dish 3 holding the sol 11 and gel 12 was not rocked by rotating the reaction chamber 2 in the gelation step S2, the solvent washing and replacement step S3, and the drying step S4, and the other conditions were the same as those of the present invention, to obtain a comparative aerogel (comparative example). Furthermore, by repeating this operation seven times, a total of eight sheets of aerogel 1 were obtained.
[0147] <Evaluation> (Observation of cracks occurring in aerogel) The aerogels obtained in the examples of the present invention and the comparative examples were visually observed. As a result, the aerogels obtained in the examples of the present invention were able to be obtained as crack-free regions over the entire surface in all 27 sheets of aerogel. On the other hand, in the aerogels obtained in the comparative examples, breakage occurred in all eight sheets of aerogel, and it was not possible to obtain aerogels capable of obtaining a square surface area of 300 mm on each side. Therefore, the aerogels obtained in the examples of the present invention were able to be obtained in a higher yield than the aerogels in the comparative examples, and were in a sound state without defects such as cracks.
[0148] (Measurement of transmittance of aerogel) The transmittance of the obtained aerogel was calculated from the spectrum data obtained using a V-670 ultraviolet-visible-near infrared spectrophotometer (manufactured by Japan Jusco Co., Ltd.) equipped with an integrating sphere. The total transmittance values when irradiating visible light with a wavelength of 550 nm to three points on the surface area of a 300 mm square that overlaps with the center (center of gravity) of the aerogel, namely, the center of the square, the corner positions of the square, and the center positions of the sides of the square (the center positions of the sides connecting the adjacent corners of the square), were calculated using the Lambert-Beer equation to obtain the total transmittance (T 550 ) was calculated. Here, the center position of the square was a position within a 50 mm square area having the same center as the square of the surface region. The corner position of the square was a position within a 50 mm square area having the same corner as the square of the surface region and overlapping with the square of the surface region. The center position of the side of the square was a position within a 50 mm square area where the center position of the side connecting the adjacent corners of the square was in the same position as the square of the surface region and overlapping with the square of the surface region. The thickness of the sample was measured using a caliper at each measurement position after measuring the total transmittance. The standard deviation of these three points of the total light transmittance for each aerogel was calculated from the total transmittance value calculated for each location in the aerogel, and the average of the obtained standard deviations was used as the standard deviation result.
[0149] As a result, as shown in FIG. 6, the aerogel of the present invention had a standard deviation of the total light transmittance (the standard deviation of the above-mentioned three points) of approximately 0.30% when irradiated with visible light having a wavelength of 550 nm, whereas the aerogel of the comparative example had a standard deviation of the total light transmittance of approximately 1.00% when irradiated with visible light having a wavelength of 550 nm.
[0150] Therefore, it was shown that the aerogel of the present invention was a large-sized aerogel without cracks. This also made it clear that the occurrence of cracks can be suppressed by using an aerogel with a small standard deviation of the total light transmittance when irradiated with visible light having a wavelength of 550 nm.
[0151] <Overall rating> It was revealed that the aerogel of the present invention has a small standard deviation of the total light transmittance when irradiated with visible light having a wavelength of 550 nm, and in this case, aerogel having a sound state without defects such as cracks can be obtained with a high yield. It is also found that the aerogel of the present invention having a small standard deviation of the total light transmittance when irradiated with visible light having a wavelength of 550 nm can be obtained by applying the manufacturing method of the present invention in which the casting dish 3 holding the sol 11 or gel 12 is rocked in one or both of the gelation step S2 and the drying step S4. [Explanation of symbols]
[0152] 1. Aerogel 10. Aerogel manufacturing equipment 11 Sol 12 Gel (wet gel) 2. Reaction chamber 3 Casting Plates 30 Casting Dish Holder 31 Bottom of the casting dish 4 Casting means 5. First solvent supply means 6 Second solvent supply means 71 Drainage means 72 Temperature adjustment means 8. Swing Mechanism S1 Sol generation process S2 Gelling process S21 Catalyst addition process S22 Casting process S23 Curing process S3 Solvent washing and replacement process S4 Drying process S41 1st process S42 2nd process S43 3rd process L1 1st liquid phase L10 First Solvent L2 2nd liquid phase L20 Second Solvent
Claims
1. An aerogel containing Si, the aerogel having a pore structure formed of a mesh-like continuous fibrous skeleton and a plurality of pores defined by the skeleton, The aerogel is It has at least a surface area of 300 mm square, and The aerogel has a standard deviation of total light transmittance of 0.60% or less when the surface region is irradiated with visible light having a wavelength of 550 nm, calculated based on a thickness of 10 mm.
2. 2. The aerogel according to claim 1, wherein the total light transmittance when irradiated with visible light is 50% or more in terms of a thickness of 10 mm.
3. 3. The aerogel of claim 1 or 2, produced by atmospheric drying.
4. a sol generating step of adding a silicon compound to an aqueous solution and generating a sol by hydrolysis; a gelling step of injecting the sol into a casting dish, crosslinking the sol in the casting dish to produce a gel, and curing the gel; a solvent washing and replacement step of supplying a first solvent having a low surface tension of 45 mN / m or less at 20° C. into the casting dish, and washing and replacing the inherent solvent present on the surface and inside of the gel with the first solvent; A method for producing an aerogel, comprising: a drying step of drying a second solvent, the second solvent having a higher specific gravity than the first solvent and undergoing two-phase separation from the first solvent, while the second solvent is being supplied to the casting dish, to produce an aerogel containing Si; At least one of the gelation step, the solvent washing and replacement step, and the drying step is performed while the sol or gel produced in the casting dish is oscillated in a lateral direction parallel to the bottom surface of the casting dish while being held in the casting dish.
5. The method for producing an aerogel according to claim 4, wherein each step from the gelling step to the drying step is carried out in the same reaction chamber.
6. The method for producing an aerogel according to claim 4, wherein at least the gelling step and the drying step among the steps from the gelling step to the drying step are performed in separate reaction chambers.
7. 7. The method for producing an aerogel according to claim 5, wherein the gelation step is performed by adjusting a concentration of water vapor contained in the atmosphere in the reaction chamber to a range of 60% or more and 100% or less with respect to a saturated water vapor pressure.
8. The method for producing an aerogel according to claim 5 or 6, wherein the drying step is performed by adjusting a vapor concentration of the solvent contained in the atmosphere in the reaction chamber to a range of 70% or more and less than 100%.
9. The method for producing an aerogel according to claim 5 or 6, wherein the drying step is performed by maintaining the atmosphere in the reaction chamber at normal pressure.
10. a casting dish in which a silicon compound is added to an aqueous solution, and a sol is generated by hydrolysis, and a crosslinking reaction is caused to generate a gel, and the gel is cured; a casting means for pouring the sol into the casting dish; a first solvent supplying means for supplying a first solvent having a low surface tension of 45 mN / m or less at 20° C. into the casting dish, and washing and replacing an inherent solvent present on the surface and inside of the gel with the first solvent; a second solvent supplying means for supplying a second solvent, the second solvent having a specific gravity greater than that of the first solvent and capable of undergoing two-phase separation from the first solvent, into the casting dish; a drying means for drying the second solvent in a state where the second solvent is supplied into the casting dish to produce an aerogel containing Si; and a rocking mechanism that rocks the sol or gel formed in the casting dish in a lateral rocking direction parallel to a bottom surface of the casting dish while the sol or gel is held by the casting dish.
Citation Information
Patent Citations
Process for producing formula feed for fish farming
JP1977050900A